Unveiling awareness: determining the university students' understanding of female reproductive rights through a validated questionnaire - Ahmed, Hina; Ashraf, Haiqa; Shahbaz, Fiza (Journal of the Pakistan Medical Association, 2025)
Objective: To compare the knowledge of medical and non-medical students regarding female reproductive rights. Method: The comparative, analytical study was conducted in Lahore, Pakistan, from April to October 2023, and comprised medical students from the Central Park Medical College, Lahore, and non-medical students from the Superior College, Lahore. Using factor analysis, validation of the self-developed questionnaire was done, and five factors were identified: supportive influence, premarital screening and stigma, conscious decision, decision about marriage, and contraceptive choices. The questionnaire's overall reliability was 0.84 using Cronbach alpha value. Data was analysed using SPSS 25. Results: Of the 500 students, 250(50%) were medical students with mean age 20.95 1.776 years, and 250(50%) were non-medical students with mean age 21.14 1.547 years. There was a statistically significant difference in knowledge level regarding women’s reproductive rights between medical and non-medical students (p<0.05). Conclusion: Significant differences were noted in the knowledge level of medical and non-medical students regarding female reproductive rights, underlining the need to create awareness among young adults. Key Words: Reproductive eights, Healthcare disparity, Unwanted pregnancy, Healthcare accessibility, Attitudes towards health, Mandatory screening, Personal autonomy.